Limits of propositionalism. Issue 7 (16th November 2016) - Grzankowski, Alex
Abstract: Propositionalists hold that, fundamentally, all attitudes are propositional attitudes. A number of philosophers have recently called the propositionalist thesis into question. It has been argued, successfully I believe, that there are attitudes that are of or about things but which do not have a propositional content concerning those things. If correct, our theories of mind will include non-propositional attitudes as well as propositional attitudes. In light of this, Sinhababu's recent attack on anti-propositionalists is noteworthy. The present paper aims to sharpen his worries and show that they fail for a range of reasons. Besides merely offering a reply, considering his challenges provides an opportunity to add clarity to this emerging area of research and it allows one to strengthen the case against propositionalism more generally.